Possibilities for secondary data use of electronic health records with WiseSpace de-identification - Vovk, Olga; Ghasempour, Ali; Piho, Gunnar; Ross, Peeter (Frontiers in Medicine, 2025)
IntroductionThe secondary use of Electronic Health Records (EHRs) holds significant potential for advancing research, public health, and innovation. However, data sharing is often limited by privacy regulations, requirements, and technical complexity. This study introduces Design Science (DS) research on the evidence-based design of WiseSpace—a tool specifically tailored to address these challenges by enabling the secure, regulation-compliant de-identification of healthcare data, particularly for non-technical users.MethodsThe research utilizes DS methodology to develop and evaluate the de-identification solution. This approach includes problem investigation through literature review, existing method and tool evaluation, and expert interviews; treatment design based on the identified challenges; treatment validation; and treatment implementation.ResultsWiseSpace provides tools for personal, identifiable health data detection, de-identification, and re-identification as well as risk assessment. The tool supports common health data standards and its intuitive user interface allows healthcare professionals, individuals, and researchers to perform data management-related tasks without requiring technical expertise.DiscussionWiseSpace addresses critical gaps in existing anonymization solutions by providing domain-specific support for healthcare data and ensuring compliance with the General Data Protection Regulation (GDPR) and the European Health Data Space (EHDS). It offers automation and risk mitigation solutions and simplifies workflow, enabling secondary data use. Use cases demonstrate the solution's utility for organizations and individuals.